2022
DOI: 10.1111/are.15975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity treatment on muscle quality and off‐flavour compounds of grass carp ( Ctenopharyngodon idella ) and black carp ( Mylopharyngodon piceus )

Abstract: To investigate the effects of short-term salinity treatment on muscle quality and earthy and musty off-flavour compounds of freshwater fish, adult grass carp (1.25 ± 0.25 kg) and black carp (1.50 ± 0.30 kg) were reared at water salinities of 0‰, 5‰ and 7.5‰for 48 h. Muscle nutrients, amino acid, and fatty acid contents, texture properties, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The contents of crude protein and crude lipid in diets and muscle were determined by a Kjeldahl nitrogen analyzer (Kjeltec 8400, FOSS, Denmark) and a Soxhlet extractor (Soxtec 8000, FOSS, Denmark), respectively. Crude ash content of diets was 3 Aquaculture Nutrition measured by combusting samples in a muffle furnace at 550 °C for 6 h. Amino acid profile in diets was analyzed using an automatic amino acid analyzer (L-8900, Hitachi, Japan) according to the method described by Qu et al [32]. The FAA composition in muscle was detected by an automatic amino acid analyzer (L-8900, Hitachi, Japan) with a lithium highperformance column using the method of Xu et al [33].…”
Section: Analysis Of Proximate Composition and Amino Acid Inmentioning
confidence: 99%
“…The contents of crude protein and crude lipid in diets and muscle were determined by a Kjeldahl nitrogen analyzer (Kjeltec 8400, FOSS, Denmark) and a Soxhlet extractor (Soxtec 8000, FOSS, Denmark), respectively. Crude ash content of diets was 3 Aquaculture Nutrition measured by combusting samples in a muffle furnace at 550 °C for 6 h. Amino acid profile in diets was analyzed using an automatic amino acid analyzer (L-8900, Hitachi, Japan) according to the method described by Qu et al [32]. The FAA composition in muscle was detected by an automatic amino acid analyzer (L-8900, Hitachi, Japan) with a lithium highperformance column using the method of Xu et al [33].…”
Section: Analysis Of Proximate Composition and Amino Acid Inmentioning
confidence: 99%
“…For example, as one of the essential amino acids, the most important physiological function of Lys is to participate in the synthesis of proteins, so it is closely related to animal growth [25]. Glu, Asp, Gly, and Ala are known as umami amino acids, and the high content of them was able to improve the quality and flavor of fish muscle [26,27]. In addition, Buchtov et al [28] suggested that high levels of essential amino acids could also improve the flavor and quality of fish muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Grass carp and black carp (Mylopharyngodon piceus) exposed to 7.5‰ for 24 h had higher levels of polyunsaturated fatty acid (PUFA) and increased muscle hardness compared with those reared in FW. 298 Nile tilapia exposed to 12‰ had increased levels of the flavourenhancing amino acids glutamic acid and proline along with EPA, DHA and PUFA content compared with fish kept in FW. 299 A rise in salinity also affected fatty acid composition in rainbow trout, where 1.7‰ increased n-3 PUFA, EPA and DHA content while decreasing monounsaturated fatty acid (MUFA) and n-6 PUFA compared with FW controls 300 and Japanese seabass (L. japonicus), where rearing at 26.2‰ increased n-3 PUFA, EPA and DHA in muscle compared with fish reared in a FW pond.…”
Section: Nutrition and Flesh Qualitymentioning
confidence: 94%
“…A short salinity treatment also influences the muscle quality and flavour of carps. Grass carp and black carp ( Mylopharyngodon piceus ) exposed to 7.5‰ for 24 h had higher levels of polyunsaturated fatty acid (PUFA) and increased muscle hardness compared with those reared in FW 298 …”
Section: Implications For Productionmentioning
confidence: 99%